A Comparative Study of Contemporary Scholars’ Views on Medieval European Science (International Journal of World Civilizations and Philosophical Studies, 2026)
This research paper investigates how medieval science has been evaluated in modern historical scholarship and its place within the broader development of scientific knowledge. Earlier historical narratives often characterized the European Middle Ages as the “Dark Ages”. They supported the discontinuity thesis, which argued that medieval thought lacked relevance to the rise of modern science. Such interpretations reduced the period to intellectual stagnation and ignored its contributions. In response, this study reviews the work of post-World War II historians who redefined medieval science and laid the foundation for the continuity thesis. The research goal is to examine how contemporary scholarship interprets the intellectual role of medieval Europe, particularly through the study of universities, scholasticism, and natural philosophy. The findings indicate that most historians now reject the notion that medieval Europe was scientifically stagnant and instead recognize its intellectual significance and long-term influence. The study concludes that the continuity thesis offers a more accurate framework, emphasizing the need for interdisciplinary and global perspectives in future research on medieval science and its connection to the Scientific Revolution.